eHealth Strategy Development: A Case Study in Tanzania - Darcy, Niamh; Elias, Mturi; Swai, Andrew; Danford, Happy; Rulagirwa, Hermes; Perera, Sriyanjit (Journal of Health Informatics in Africa, 2015)
Many developing countries have used different frameworks, some ad hoc and some more formal, to develop their national eHealth strategies. There is increasing interest in eHealth strategy in developing countries, as well as a move to a more integrated and less fragmented set of eHealth solutions that contribute to health objectives and outcomes. Developing a national eHealth Strategy from the national health sector priorities should lead to implementation of sustainable eHealth solutions. Some existing frameworks for developing national eHealth strategies can be difficult to implement effectively. This paper presents how an alternative country eHealth Strategy framework was applied in Tanzania to develop the Tanzania eHealth Strategy 2013–2018. This alternative framework begins with reviewing Tanzania’s Health Sector Strategic Plan III (2009–2015) priorities and goals, from which the eHealth strategy’s priorities and goals are developed. The process is informed by the current state of eHealth and the proposed future state of eHealth. It defines the vision, mission, and guiding principles, well-defined strategic objectives and actions, a high-level roadmap, and an appropriate monitoring and evaluation (M&E) framework. The application of this alternative eHealth strategy development framework is based on theories of business process re-engineering, strategy development, and complex systems analysis.